Enjeux de la reconstruction : recoudre le tissu urbain, renouer le lien social - Murielle Hladik (Ebisu: Études Japonaises, 2012)
What are the ethical, economic, environmental and social issues surrounding post-disaster reconstruction? Following emergency intervention, the task of reconstruction leads to new questions regarding security: Is ”zero risk” conceivable? How is the affected community to repair and maintain the social cohesion that previously existed in the area, but which has been totally devastated? Is it possible to stimulate hope and construct a foundation for a new beginning?